Analisis Pengembangan Potensi Wana Wisata Bukit Pinus - Fairuuz, Zalfaa; Yudha, Agus Tri Sapta; Nawangsari, Ertien Rining (Peneliti.net, 2023)
Wana Wisata Bukit Pinus is one of the most famous tourist objects in Carangwulung Village. This tourist attraction presents natural attractions that are still beautiful. This tourism potential is the result of collaboration between community groups and Perhutani Jombang district. Tourism potential requires an appropriate tourism development strategy in order to continue to develop and survive its existence. This problem is the background of this research, namely to analyze how to develop the potential of the Wana Wisata Bukit Pinus, so that it can become an evaluation material in the future in developing tourism in Carangwulung Village. The results of the analysis use the tourism component theory according to (Cooper 2016) which includes: 1) attraction, 2) accessibility, 3) amenities, 4) Ancillary Services, shows that the development of tourism in the Bukit Pinus Tourism Area still has obstacles. In this study used a qualitative description method with data collection techniques through observation, interviews, and documentation.